Hydraulic stability of micro injections using a two-layered 8-hole solenoid injector with PODE. (1st August 2021) - Röll, A.; Luo, F.; O'Connell, N.; Lechner, R.; Wang, C.; Brautsch, M.
Highlights: PODE shows an almost identical injection behavior compared to base diesel fuel. The deviations from cycle to cycle are very small. A correlation between the discharge coefficient and the Reynolds number for different energizing times was determined empirically. PODE could be used as a suitable replacement for diesel as pilot fuel in dual fuel engines. Abstract: The aim of this study was to investigate the hydraulic stability of micro injections when using polyoxymethylene dimethyl ether (PODE) as pilot fuel for a dual fuel heavy-duty stationary engine. A two-layered 8-hole solenoid injector with an injection angle of 75° was used for the investigation. The challenge with regard to the investigated type of diesel-ignited gas engines is that the injector has to provide a stable injection for both full-diesel mode and dual fuel mode. The stability of the injection was evaluated using the following values: The injection rate, injection gravimetric quantity, injected amount of energy, standard deviation of the injection quantity, coefficient of variation of the injected quantity, the momentum flux, injection duration and injection delay at various pressures and energizing times with neat base diesel fuel, neat PODE and a 50- vol-% PODE-diesel-blend. PODE was found to have a similar gravimetric total injection rates of all holes compared to base diesel fuel with almost the same standard deviation. At higher injection pressures and longer energizing times, the influence of the fuel on the injection quantity becomes more relevant. The influence of the fuel on the injection delay and injection duration was found to be small. An empiric correlation between the discharge coefficient and the Reynolds number was determined which can be used to calculate the discharge coefficient. In summary, we can conclude that with regard to the hydraulic injection characteristics, PODE could be used as a suitable replacement for diesel as pilot fuel in dual fuel engines.